The WTO and direct taxation - Michael Daly (World Trade Organization (WTO), 2005)
It contains a summary of disputes concerning income tax measures that have arisen at the WTO since its establishment, with special attention to the protracted dispute between the EC and the US over the latter's FSC/ETI schemes.
Keywords: F13; H25; K34; 330; direct taxation; WTO rules; foreign sales corporation (FSC); trade disputes